The Issue of the Sacred in Freemasonry: Intolerance, Controversies and Approaches - Rodrigues de Souza, Fernando (2023)
Freemasonry is based on illuminist and libertarian principles that guarantee the institution a secular character and tolerance, allowing its members to practice religious freedom. However, the last three centuries were marked by several demonstrations of intolerance between the Masonic institution and the different religions, internal disputes that resulted in schisms and that demonstrate contradiction between the theory and the practical application of such principles.  This text aims to analyze some of these tensions, bringing new considerations about the religious issue and its relationship with Freemasonry and the challenges for the future.